2019
DOI: 10.1111/apt.15540
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of autoimmune atrophic gastritis: a prospective, single centre, long‐term experience

Abstract: Summary Background Autoimmune atrophic gastritis (AAG) is an immune‐mediated disorder characterised by destruction of gastric oxyntic mucosa Aim To explore gastric histopathological evolution in a cohort of AAG patients over a prolonged follow‐up Methods Single centre prospective study enrolling consecutive patients with histologically confirmed AAG between 2000 and 2018. All AAG patients undergoing endoscopic follow‐up every 1‐3 years were classified as having stages 1, 2 or 3 according to atrophy severity (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 40 publications
(85 reference statements)
4
54
2
6
Order By: Relevance
“…In both cases, the nodular lesions shrank over time and were surrounded by atrophic mucosa, in agreement with the progression of gastric atrophy. Although a recent study reported that the histopathological progression of gastric atrophy from early-stage AIG occurred within three years, the relevant changes in the endoscopic appearances have not been determined (12). The findings in our cases indicate that the nodular lesions in non-atrophic areas of the gastric corpus are a manifestation of gastric inflammation and atrophy during the progress of early-stage AIG.…”
Section: Discussioncontrasting
confidence: 67%
“…In both cases, the nodular lesions shrank over time and were surrounded by atrophic mucosa, in agreement with the progression of gastric atrophy. Although a recent study reported that the histopathological progression of gastric atrophy from early-stage AIG occurred within three years, the relevant changes in the endoscopic appearances have not been determined (12). The findings in our cases indicate that the nodular lesions in non-atrophic areas of the gastric corpus are a manifestation of gastric inflammation and atrophy during the progress of early-stage AIG.…”
Section: Discussioncontrasting
confidence: 67%
“…In this scenario, the background of active H. pylori inflammation is likely to play a confounding role that may have hampered the accurate detection of gastric dysplasia. Nevertheless, the unexpected high baseline prevalence of dysplasia may be partially justified by the concomitant presence of AAG in a considerable number of our patients, in accordance with results from a recent study showing that in the presence of AAG the risk of developing more advanced stages on long-term follow-up is greater in patients with more severe gastric lesions[ 8 ]. The overlap between autoimmune and H. pylori -induced chronic gastritis may presumably be associated with a more severe gastric injury, especially in older subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Helicobacter pylori ( H. pylori ) infection has been associated with premalignant gastric conditions (PGC), such as chronic atrophic gastritis and intestinal metaplasia (IM), which are strongly associated with dysplasia and Lauren intestinal-type of gastric carcinoma (GC)[ 1 - 7 ]. Autoimmune atrophic gastritis (AAG) is responsible for progressive mucosal atrophy (antrum-sparing) with or without IM[ 8 ]. Many studies have attributed gastric carcinogenesis to both genetic predisposition and H. pylori -induced gastric inflammation[ 9 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, iron deficiency anaemia was more common in younger female patients, whereas pernicious anaemia was more common in older male patients. These findings may be explained by the slow evolution of AAG, that may take several years to progress [1,33,34]. It is reasonable to assume that iron deficiency characterises earlier disease stages, in which hypo-achlorhydria causes iron malabsorption, even if additional unknown immunological factors may have a role.…”
Section: Discussionmentioning
confidence: 99%